THE MIDDLE-INCOME TRAP: IS THERE A WAY OUT FOR ASIAN COUNTRIES? - Raisal Fahrozi Lubis; Putu Mahardika Adi Saputra (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This study aims at investigating the phenomena of the middle-income trap found in developing Asian countries, such as China, India, Indonesia, Malaysia, the Philippines, and Thailand. The effects of some of the determinant variables of per capita income, such as government expenditure, investment expenditure, high technology exports, factors of human capital (enrollment rates in secondary and tertiary education), and the dependency ratio are analyzed by using a factor analysis and regression analysis. The factor analysis is used to reduce the variable of the publics’ enrollment rate in secondary and tertiary education into the variable of the human capital factor. The findings of the study reveal that some variables, namely government expenditure, investment expenditure, high technology exports, and the factors of human capital, have positive effects in increasing the per capita income of a country. The variable of the dependency ratio, on the other hand, has a negative effect on a country’s per capita income.Keywords: Asian, middle-income trap, panel analysis, and slowdown.